A Perspective on the Use of Sexed Semen to Reduce the Number of Surplus Male Dairy Calves in Ireland: A Pilot Study - Balzani, Agnese; Aparacida Vaz do Amaral, Cintia; Hanlon, Alison (Frontiers in Veterinary Science, 2021)
The production of surplus male offspring illustrates a socio-ethical concern in the dairy industry. In, this article, we highlight the animal health and welfare implications of production outputs for surplus dairy calves, namely veal production, dairy calf to beef production and euthanasia. Moreover, we present a pilot study focus on exploring the perception of key industry actors within the dairy industry in Ireland regarding the use of sexed semen as a mitigation strategy to reduce the production of surplus male dairy calves. A pilot survey was completed by farmers (n = 6), veterinarians (n = 17), and dairy farm advisors (n = 11). All the veterinarians, 80% of the farmers, and 62% of the advisors believed that the use of sexed semen had a positive influence on herd welfare. All participants identified the same barriers to the implementation of sexed semen: lower conception rate, low availability, and high price. The reviewed literature highlights the importance of tailored communication to support knowledge exchange between stakeholders and key industry actors such as dairy farmers, their veterinarians and advisors. Research to understand stakeholders’ perception is pivotal to address socio-ethical concerns such as the surplus male dairy calves.